2011
DOI: 10.1007/s00423-011-0827-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction and clinical results 10 years after modified open thoracoplasty for pectus deformities

Abstract: This study retrospectively shows that this modification of the Ravitch approach is a safe and effective treatment option for pectus deformities with long-term satisfactory results for the patients without the need for bar removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Psychological symptoms resulting from body image issues are common and can severely curtail the quality of life of some individuals (2). Physiological limitations caused by this deformity, particularly cardiovascular (3) and pulmonary impairments (4), have meant that correction of pectus excavatum can play a major role in improving the physical activity and quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological symptoms resulting from body image issues are common and can severely curtail the quality of life of some individuals (2). Physiological limitations caused by this deformity, particularly cardiovascular (3) and pulmonary impairments (4), have meant that correction of pectus excavatum can play a major role in improving the physical activity and quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, Sternal allogeneic bone grafts have proven to be an effective and biologically well-tolerated option for sternal replacement. 5,23,28 In addition, several reports have questioned the necessity of radiographic studies with the use of chest x-rays which are taken after instrumentation in or around the thoracic cavity which was driven by concerns for radiation exposure, particularly in the pediatric population with a retrospective study which demonstrated that the postoperative chest x-rays were unnecessary following bar placement unless respiratory symptoms were present. 29 Invariably also, cardiac magnetic resonance imaging is currently been the reference standard for anatomic and functional cardiac assessments as several PE defects are more than likely to impair right ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] However, the depression on the sternum can displace the heart; cause a decrease in the right ventricular functions of the heart and also a decrease in pulmonary functions too due to the decrease in thoracic volume. 2,3 Nevertheless, PE cases have mostly been a cosmetic defect including issues regarding body image which may significantly impact a person's quality of life, low self-esteem, and increased psychosocial problems with PE patients mostly complaining of chest pain, difficulty breathing, decreased cardiac output and decreased exercise capacity depending on its severity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations